PERAN STRATEGIS SATUAN PENGAWAS INTERNAL DALAM TATA KELOLA DAN AKUNTABILITAS SEBAGAI PENJAGA INTEGRITAS RUMAH SAKIT - Isniati Setia Ningrum (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The increasing complexity of hospital governance, the advancement of healthcare service digitalization, and the high risk of administrative irregularities, regulatory non-compliance, and fraudulent practices require stronger and more effective internal control systems. However, studies examining the strategic role of the Internal Supervisory Unit (Satuan Pengawas Internal/SPI) in maintaining organizational integrity and enhancing hospital accountability remain limited, particularly regarding its function as a strategic management partner. This study aims to analyze the strategic role of SPI in supporting good hospital governance, strengthening accountability, and maintaining the integrity of healthcare organizations. The study employed a qualitative descriptive approach through a literature review by examining various sources, including scientific journals, books, regulations, and documents related to hospital governance and internal supervision. Data were analyzed descriptively to identify the functions, challenges, and contributions of SPI within hospital management systems. The findings indicate that SPI serves not only as an internal supervisory body but also as an evaluator, consultant, and risk controller contributing to fraud prevention, improved regulatory compliance, strengthened internal control systems, and enhanced organizational transparency and efficiency. Nevertheless, the effectiveness of SPI still faces several challenges, including limitations in human resources, independence, auditor competencies, and the increasing complexity of healthcare service systems. Therefore, optimizing SPI functions, improving institutional capacity, and strengthening management support can position SPI as a guardian of organizational integrity capable of reinforcing accountability and increasing public trust in hospital services. ABSTRAK Meningkatnya kompleksitas tata kelola rumah sakit, perkembangan digitalisasi layanan kesehatan, serta tingginya risiko penyimpangan administrasi, ketidakpatuhan regulasi, dan praktik fraud menuntut penguatan sistem pengawasan internal yang efektif. Namun, kajian mengenai peran strategis Satuan Pengawas Internal (SPI) dalam menjaga integritas organisasi dan meningkatkan akuntabilitas rumah sakit masih terbatas, terutama pada fungsi SPI sebagai mitra strategis manajemen. Penelitian ini bertujuan menganalisis peran strategis SPI dalam mendukung tata kelola rumah sakit yang baik (good hospital governance), memperkuat akuntabilitas, serta menjaga integritas organisasi pelayanan kesehatan. Penelitian menggunakan pendekatan deskriptif kualitatif melalui kajian literatur dengan menelaah berbagai sumber berupa jurnal ilmiah, buku, regulasi, dan dokumen yang berkaitan dengan tata kelola rumah sakit serta pengawasan internal. Analisis dilakukan secara deskriptif untuk mengidentifikasi fungsi, tantangan, dan kontribusi SPI dalam sistem manajemen rumah sakit. Hasil kajian menunjukkan bahwa SPI tidak hanya berfungsi sebagai pengawas internal, tetapi juga sebagai evaluator, konsultan, dan pengendali risiko yang berperan dalam pencegahan fraud, peningkatan kepatuhan terhadap regulasi, penguatan sistem pengendalian internal, serta peningkatan transparansi dan efisiensi organisasi. Di sisi lain, efektivitas SPI masih menghadapi berbagai kendala, antara lain keterbatasan sumber daya manusia, independensi, kompetensi auditor, serta kompleksitas sistem pelayanan kesehatan. Dengan optimalisasi fungsi, peningkatan kapasitas, dan dukungan manajemen, SPI berpotensi menjadi penjaga integritas organisasi yang mampu memperkuat akuntabilitas dan meningkatkan kepercayaan masyarakat terhadap pelayanan rumah sakit.